Rethinking Atlantic empire : Christopher Schmidt-Nowara's histories of nineteenth-century Spain and the Antilles - Eastman, Scott, 1971-; Jacobson, Stephen (Stephen H.); Schmidt-Nowara, Christopher, 1966-2015 (Studies in Latin American and Spanish history., 2021)
"In recent years, the historiography of nineteenth-century Spain and Latin America has been invigorated by interdisciplinary engagement with scholars working on topics such as empire, slavery, abolition, race, identity, and captivity. No scholar better exemplified these developments than Christopher Schmidt-Nowara, a specialist on Spain and its Caribbean colonies in Cuba and Puerto Rico. A brilliant career was cut short in 2015 when he died at the age of 48. Rethinking Atlantic Empire takes Schmidt-Nowara's work as a point of departure, charting scholarly paths that move past reductive national narratives and embrace transnational approaches to the entangled empires of the Atlantic world"--